2017
DOI: 10.1158/1535-7163.mct-17-0423
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Model for Quantitative, Real-Time Evaluation of Convection-Enhanced Delivery (RT-CED) Using an 18[F]-Positron Emitting, Fluorescent Derivative of Dasatinib

Abstract: The blood brain barrier can limit the efficacy of systemically delivered drugs in treating neurological malignancies; therefore, alternate routes of drug administration must be considered. The Abl-kinase inhibitor, dasatinib, is modified to give compound 1 ([18F]-1) so that 18F-positron emission tomography (PET) and fluorescent imaging can both be used to observe drug delivery to murine orthotopic glioma. In vitro western blotting, binding studies (IC50 = 22 ± 5 nM), and cell viability assays (IC50 = 46 ± 30 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…These properties make compound 1 an ideal candidate for evaluating different methods of HDAC delivery in vivo. Solutions of [ 18 F]-1 (300 μCi, in 1% DMSO/1× PBS) are delivered to mice through different methods, including CED, 26 to illustrate the use of quantitative imaging in drug delivery, [ 18 F]-1 was delivered to naive mice by CED, 26 intraperitoneally (Figure 4), and intravenously (IV, not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These properties make compound 1 an ideal candidate for evaluating different methods of HDAC delivery in vivo. Solutions of [ 18 F]-1 (300 μCi, in 1% DMSO/1× PBS) are delivered to mice through different methods, including CED, 26 to illustrate the use of quantitative imaging in drug delivery, [ 18 F]-1 was delivered to naive mice by CED, 26 intraperitoneally (Figure 4), and intravenously (IV, not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The foundational in vivo efforts 17,19,23,28,31 of Souweidane and colleagues have demonstrated the feasibility of interstitial infusion to the rat brainstem. In an early study, 19 they validated the feasibility of delivering 20 kDa of FITC-dextran beads to the brainstem by means of acute CED and by chronic osmotic pump delivery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Interstitial infusion by CED to the brainstem has been proven safe and feasible in multiple animal models, and recently a phase I clinical trial in children with DIPG validated this as safe in human patients. 9,17,19,23,28,31 Post hoc analyses after CED have demonstrated that therapeutic agents achieve high concentrations in the regional parenchyma and adjacent white matter tracts, with negligible efflux in the presence of an intact BBB. 6,7,22,32 Other interstitial infusion approaches distribute infusate by other mechanisms, including osmotic pump delivery, which relies solely on osmotic gradients after catheter insertion to encourage distribution within the target tissue.…”
mentioning
confidence: 99%
“…A few studies have used coinfusion with gadolinium to monitor infusate distribution (176,177). Wang et al (93) investigated CED of an 18 [F]-positron-emitting, fluorescent derivative of the Abl-kinase inhibitor dasatinib in a mouse glioma model. Similar to other studies (178,179), the main purpose of coadministration of the fluorescent agent is to monitor drug distribution in experimental settings.…”
Section: Convection-enhanced Deliverymentioning
confidence: 99%